Mathematic simulation of the process of prediction probability as the basis of the choice of «perception unit»/ - Приснякова Л. M.; Присняков, В. Ф. (Proceedings of National Aviation University (archive), 1999)
Considered is the theoretical dependence of sensation and irritation association which agrees with the known experimental data. Confirmed is connection between time constant of processing information by memory and by brain alpha-rythms. Confirmed are also perspectives of mathematical description of processes going in human brain reprocessing information